Honorific mismatches of coordinate subjects in Korean - Kim, Jeong-Seok; Jung, Duk-Ho; Lee, Jin Hyung (Canadian journal of linguistics, 2023)
In this article, we explore whether hierarchy and linearity conspire to affect agreement. The data come from an experimental study of honorific agreement between verbal si and coordinate subjects in Korean. We focus on computing the mismatch driven by honorifically mixed conjuncts. Unlike South Slavic gender agreement, Korean has neither Resolved Agreement nor First Conjunct Agreement. Only Last Conjunct Agreement is attested in Korean honorification. We show that honorific agreement within coordinate subjects is triggered only when the honorific verbal si appears, which is substantially different from the case with the honorific nominal nim. We also show that acceptability significantly decreases when the last conjunct of coordinate subjects is incongruous with an honorific verb. We thus argue that verbal honorific agreement with Korean coordinate subjects is sensitive to linear order, mimicking South Slavic gender agreement.